British Columbia & the Canadian Rockies 2024 - Bujan, Bianca (Lonely Planet guidebooks., 2024)
Lonely Planet's British Columbia and the Canadian Rockies is our most comprehensive guide that extensively covers all the region has to offer, with recommendations for both popular and lesser-known experiences. Explore in Jasper National Park; ski at Whistler and marvel at Lake Louise; all with your trusted travel companion. Inside Lonely Planet's British Columbia and the Canadian Rockies Travel Guide: Lonely Planet's Top Picks - a visually inspiring collection of the destination's best experiences and where to have them Itineraries help you build the ultimate trip based on your personal needs and interests Local insights give you a richer, more rewarding travel experience - whether it's history, people, music, landscapes, wildlife, politics Eating and drinking - get the most out of your gastronomic experience as we reveal the regional dishes and drinks you have to try Toolkit - all of the planning tools for solo travelers, LGBTQIA+ travelers, family travelers and accessible travel Color maps and images throughout Language - essential phrases and language tips Insider tips to save time and money and get around like a local, avoiding crowds and trouble spots Covers Alberta, Edmonton, Calgary, British Columbia, Vancouver, Whistler, Yukon Territory, Whitehorse and more!